Initial-boundary-value problems for quasilinear degenerate hyperbolic equations with damping. Neumann problem - Tedeev, A. F. (Ukrains’kyi Matematychnyi Zhurnal, 2006)
We study the behavior of the total mass of the solution of Neumann problem for a broad class of degenerate parabolic equations with damping in spaces with noncompact boundary. New critical indices for the investigated problem are determined.